2010
DOI: 10.1089/dia.2010.0085
|View full text |Cite
|
Sign up to set email alerts
|

Association of Interleukin-10 Polymorphisms with Cytokines in Type 2 Diabetic Nephropathy

Abstract: IL-10-(-592) promoter polymorphisms may influence IL-10 and MCP-1 production, which may be an indicator of nephropathy risk in Taiwanese T2DM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…IL-10 levels increased in IL-10-(−592C/C) genotype compared to IL-10-(−592A/A) and IL-10-(−592A/C) genotypes in DN patients while such difference was not found in T2DM patients without nephropathy. Similar to our findings, IL-10-(-592C/A) genotype distribution didn't differ between T2DM patients with or without nephropathy and IL-10 (-592C/A) genotype revealed significant association with cytokine expressions in DN patients [9,14,15]. Twenty-eight polymorphisms occur in the promotor region of IL-10 gene, these polymorphisms were found to affect gene transcription and expression.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…IL-10 levels increased in IL-10-(−592C/C) genotype compared to IL-10-(−592A/A) and IL-10-(−592A/C) genotypes in DN patients while such difference was not found in T2DM patients without nephropathy. Similar to our findings, IL-10-(-592C/A) genotype distribution didn't differ between T2DM patients with or without nephropathy and IL-10 (-592C/A) genotype revealed significant association with cytokine expressions in DN patients [9,14,15]. Twenty-eight polymorphisms occur in the promotor region of IL-10 gene, these polymorphisms were found to affect gene transcription and expression.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, high concentrations of IL-10 were found associated with severe sepsis protecting patients from death while low levels were found in nonsurvivors [8]. IL-10 polymorphic variants are linked with cytokine production and are involved in many chronic inflammatory diseases, including T2DM [9]. In this investigation, we aimed to study the association of IL-10 (−592A/C) gene polymorphism with IL-10 level in T2DM with and without DN.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Wang et al [5] identified a new amino acid change (V385I) that is associated with type 2 diabetic nephropathy. In case of IL-10, polymorphism (-592) in promoter region influence IL-10 and MCP-1 production, which may be an indicator of type 2 diabetic nephropathy risk in Taiwanese patients [6] . Tumour necrosis factor: Gene for tumour necrosis factor (TNF)-α is highly polymorphic and is located on chromosome 6p.…”
Section: Inflammatory Cytokines Gene Variantsmentioning
confidence: 99%
“…Similarly, Ezzidi et al (2009) reported an association between the T allele of IL-10 -819T/C and the development of type 2 diabetes in a Tunisian population, while Mtiraoui et al (2009) summarized that genetic variations in the IL-10 promoter could affect the risk of nephropathy in patients with type 2 diabetes. Kung et al (2010) also reported a significant association between the -592A/C polymorphism in IL-10 and type 2 diabetic nephropathy, via altered IL-10 production. However, these results were not observed in two studies; that is, IL-10 polymorphisms were not correlated with susceptibility to type 2 diabetic nephropathy (Arababadi et al, 2012;Erdogan et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
“…Another study reported that increased serum concentrations of inflammatory cytokines are correlated with the development of diabetic nephropathy (Konenkov et al, 2015). A few studies have reported the role of the IL-10 -592C/A, -819C/T, and -1082G/A polymorphisms in susceptibility to diabetic nephropathy, but with inconsistent results (Babel et al, 2006;Mtiraoui et al, 2009;Kung et al, 2010;Arababadi et al, 2012;Erdogan et al, 2012). In this study, we have investigated the influence of the IL-10 -592C/A, -819C/T, and -1082G/A polymorphisms on the risk of diabetic nephropathy in a Chinese population.…”
Section: Introductionmentioning
confidence: 99%